Prevalences of allergic disorders in children with terra firma-forme dermatosis - Gurbuz Akcay; Yaşar Topal; Osman Aydın (Wolters Kluwer Medknow Publications, 2021)
Background: Terra firma-forme dermatosis (TFFD) is a clinical condition that may be defined as a dirty appearance of skin. Although it has been defined for many years, its clinical value is not well known. Objective: We aimed to determine the prevalence of allergic disorders (asthma, allergic rhinitis, and eczema) to investigate if this clinical condition is associated with allergic disorders in children with TFFD. Materials and Methods: A questionnaire descriptive of allergic disorders [International Study of Asthma and Allergies in Children (ISAAC)] was applied to all children diagnosed with TFFD at the pediatric clinics during a 6-month period specified for the study. The results were compared with the two ISAAC studies that have been previously conducted in our region. Results: The prevalence of TFFD among 1695 children examined at our outpatient clinic was found to be 3.18% (n = 54). The youngest of the children was 6 months old and the oldest 13 years, with an average age of 6.08 ± 2.69 years. Our study group had significantly greater rates and intensities of lifetime wheezing, wheezing in the last 12 months (current wheezing), lifetime allergic rhinitis, allergic rhinitis in the last 12 months; and the rate of physician-diagnosed allergic rhinitis compared to the comparator groups (P < 0.005). Conclusions: The results support the view that TFFD may be a sign of associated asthma and allergic rhinitis.